Adhesive tape and adhesive composition

By adjusting the composition of the acrylic copolymer and adding additives, the shear storage modulus and loss tangent of the adhesive layer were optimized, solving the problem of insufficient adhesive strength of the adhesive tape under high temperature conditions and achieving excellent adhesion and flexibility under high temperature conditions.

CN120897969APending Publication Date: 2025-11-04SEKISUI CHEMICAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480022585.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-25
Filing Date
2024-07-19
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing adhesive tapes have insufficient bonding strength at high temperatures, failing to meet the heat resistance requirements of electronic devices and automotive components.

Method used

An adhesive layer containing a specific acrylic copolymer is used, and the range of shear storage modulus and loss tangent at 150°C is adjusted to improve the cohesiveness of the adhesive layer. This includes adjusting the proportion of alkyl acrylate structural units, the content of polar functional group monomers and weight-average molecular weight, and adding silane coupling agents and tackifying resins.

Benefits of technology

It significantly improves the adhesive strength of the tape in high-temperature environments, ensuring sufficient cohesion and flexibility under high-temperature conditions, and is suitable for fixing electronic devices and automotive components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The purpose of the present invention is to provide an adhesive tape having excellent adhesive force in a high-temperature environment. The purpose of the present invention is also to provide an adhesive composition having excellent adhesive force in a high-temperature environment. The present invention is an adhesive tape having an adhesive layer, the adhesive layer containing an acrylic copolymer, the shear storage modulus of the adhesive layer at 150 DEG C measured by dynamic viscoelasticity measurement at a measurement frequency of 1 Hz being 8.0 * 104 Pa to 3.0 * 105 Pa, and the shear storage modulus of the adhesive layer at 150 DEG C being 3.0 * 105 Pa to 3.0 * 105 Pa. The loss tangent (tan [delta]) at 150 DEG C as measured by dynamic viscoelasticity measurement at a measurement frequency of 1 Hz is 0.10-0.40 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to adhesive tapes. Additionally, this invention relates to adhesive compositions. Background Technology

[0002] Adhesive tapes containing adhesive layers have been widely used for fixing components in electronic devices, vehicles, homes, and building materials (e.g., Patent Documents 1-3). Specifically, adhesive tapes are used, for example, to bond a cover plate for protecting the surface of a portable electronic device to a touch panel module or a display panel module, or to bond a touch panel module to a display panel module.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-052050

[0006] Patent Document 2: Japanese Patent Application Publication No. 2015-021067

[0007] Patent Document 3: Japanese Patent Application Publication No. 2015-120876 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] The requirements for the heat resistance of adhesive tapes used to fix electronic equipment components and automotive components have been increasing year by year. In recent years, the requirement for adhesive strength at high temperatures approaching 100°C has been growing. However, in the case of conventional adhesive tapes, the cohesive force of the adhesive layer decreases at high temperatures, sometimes resulting in insufficient adhesive strength.

[0010] The object of this invention is to provide an adhesive tape with excellent adhesion under high-temperature conditions. Furthermore, the object of this invention is to provide an adhesive composition with excellent adhesion under high-temperature conditions.

[0011] Methods for solving problems

[0012] This disclosure 1 relates to an adhesive tape having an adhesive layer comprising an acrylic copolymer, wherein the shear storage modulus of the adhesive layer at 150°C, as measured by dynamic viscoelasticity determination at a frequency of 1 Hz, is 8.0 × 10⁻⁶. 4 Pa or higher and 3.0 × 10 5 Pa is less than 0.10, and the loss tangent (tanδ) at 150°C, measured by dynamic viscoelasticity measurement at a frequency of 1 Hz, is greater than or equal to 0.10 and less than or equal to 0.40.

[0013] This disclosure 2 relates to the adhesive tape of this disclosure 1, wherein the acrylic copolymer has structural units derived from alkyl (meth)acrylates, the structural units derived from alkyl (meth)acrylates comprising structural units of alkyl (meth)acrylates derived from alcohols having 1 or more and 4 or less carbon atoms, the content of the structural units of alkyl (meth)acrylates derived from alcohols having 1 or more and 4 or less carbon atoms is 50% by mass or more and 100% by mass or less, and the content of the structural units of alkyl (meth)acrylates derived from alkyl (meth)acrylates in the acrylic copolymer is 50% by mass or more and 90% by mass or less.

[0014] This disclosure 3 relates to the adhesive tape of this disclosure 2, wherein the structural unit derived from alkyl methacrylate comprises a structural unit of alkyl methacrylate derived from an alcohol having 1 or more and 2 or less carbon atoms, and the content of the structural unit of alkyl methacrylate derived from an alcohol having 1 or more and 2 or less carbon atoms is 10% by mass or more and 80% by mass or less.

[0015] This disclosure 4 relates to adhesive tapes of disclosures 1, 2 or 3, wherein the acrylic copolymer has structural units derived from monomers containing polar functional groups, and the acrylic copolymer contains structural units derived from monomers containing polar functional groups in an amount of 3% by mass or more and 15% by mass or less.

[0016] This disclosure 5 relates to the adhesive tape of this disclosure 4, wherein the structural unit derived from the monomer containing a polar functional group comprises at least one structural unit selected from structural units derived from a carboxyl-containing monomer and structural units derived from a hydroxyl-containing monomer.

[0017] This disclosure 6 relates to adhesive tapes of disclosures 1, 2, 3, 4 or 5, wherein the acrylic copolymers described herein have structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds.

[0018] This disclosure 7 relates to the adhesive tape of this disclosure 6, wherein the acrylic copolymer contains structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds in a proportion of 5% by mass or more and 50% by mass or less.

[0019] This disclosure 8 relates to adhesive tapes of disclosures 1, 2, 3, 4, 5, 6 or 7, wherein the weight-average molecular weight of the aforementioned acrylic copolymer is 750,000 or more and less than 1,500,000.

[0020] This disclosure 9 relates to adhesive tapes of disclosures 1, 2, 3, 4, 5, 6, 7 or 8, wherein the adhesive layer further contains a silane coupling agent.

[0021] This disclosure 10 relates to the adhesive tape of this disclosure 9, wherein the content of the silane coupling agent is 0.1 parts by mass or more and 3.0 parts by mass or less relative to 100 parts by mass of the acrylic copolymer described above.

[0022] This disclosure 11 relates to adhesive tapes of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, wherein the adhesive layer further contains a tackifying resin.

[0023] This disclosure 12 relates to the adhesive tape of this disclosure 11, wherein the tackifying resin comprises at least one selected from terpene phenol resins, rosin resins and xylene resins.

[0024] This disclosure 13 relates to an adhesive tape of disclosure 11 or 12, wherein the content of the tackifying resin is 20 parts by weight or less relative to 100 parts by weight of the acrylic copolymer described above.

[0025] This disclosure 14 relates to adhesive tapes of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, wherein the gel content of the adhesive layer is 10% by mass or more and 85% by mass or less.

[0026] This disclosure 15 relates to adhesive tapes of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, wherein the thickness of the adhesive layer is 5 μm or more and 200 μm or less.

[0027] This disclosure 16 relates to an adhesive tape of disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, having a substrate.

[0028] This disclosure 17 relates to the adhesive tape of this disclosure 16, wherein the substrate comprises at least one selected from nonwoven fabric, polyester film, polyimide film, polyamide film, polyetheretherketone film, polyphenylene ether film and polyphenylene sulfide film.

[0029] This disclosure 18 relates to adhesive tapes of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17, wherein the overall thickness of the aforementioned adhesive tape is 50 μm or more and 200 μm or less.

[0030] This disclosure 19 relates to adhesive tapes of disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18, used for securing electronic device components or vehicle components.

[0031] This disclosure 20 relates to an adhesive tape having an adhesive layer comprising an acrylic copolymer having structural units derived from alkyl (meth)acrylates, structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds, and structural units derived from monomers containing polar functional groups. The structural units derived from alkyl (meth)acrylates include structural units of alkyl (meth)acrylates derived from alcohols having 1 or more and 4 or fewer carbon atoms. The proportion of the structural units derived from alkyl (meth)acrylates having 1 or more and 4 or fewer carbon atoms is 50% by mass or more and 100% by mass or less. The proportion of the structural units derived from alkyl (meth)acrylates in the acrylic copolymer is 50% by mass or more and 90% by mass or less. The proportion of the structural units derived from monomers containing polar functional groups in the acrylic copolymer is 3% by mass or more and 15% by mass or less. The weight-average molecular weight of the acrylic copolymer is 750,000 or more and less than 1,500,000.

[0032] This disclosure 21 relates to the adhesive tape of this disclosure 20, wherein the structural unit derived from alkyl (meth)acrylate comprises a structural unit of alkyl (meth)acrylate derived from an alcohol having 1 or more and 2 or less carbon atoms, and the proportion of the structural unit of alkyl (meth)acrylate derived from an alcohol having 1 or more and 2 or less carbon atoms is 10% by mass or more and 80% by mass or less.

[0033] This disclosure 22 relates to adhesive tapes of disclosure 20 or 21, wherein the structural units derived from monomers containing polar functional groups comprise at least one structural unit selected from structural units derived from carboxyl-containing monomers and structural units derived from hydroxyl-containing monomers.

[0034] This disclosure 23 relates to adhesive tapes of disclosures 20, 21 or 22, wherein the acrylic copolymer contains structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds in a proportion of 5% by mass or more and 50% by mass or less.

[0035] This disclosure 24 relates to adhesive tapes of disclosures 20, 21, 22 or 23, wherein the adhesive layer further contains a silane coupling agent.

[0036] This disclosure 25 relates to the adhesive tape of this disclosure 24, wherein the content of the silane coupling agent is 0.1 parts by mass or more and 3.0 parts by mass or less relative to 100 parts by mass of the acrylic copolymer described above.

[0037] This disclosure 26 relates to adhesive tapes of disclosures 20, 21, 22, 23, 24 or 25, wherein the adhesive layer further contains a tackifying resin.

[0038] This disclosure 27 relates to the adhesive tape of this disclosure 26, wherein the tackifying resin comprises at least one selected from terpene phenol resins, rosin resins and xylene resins.

[0039] This disclosure 28 relates to an adhesive tape of this disclosure 26 or 27, wherein the content of the tackifying resin is 20 parts by weight or less relative to 100 parts by weight of the acrylic copolymer described above.

[0040] This disclosure 29 relates to adhesive tapes of disclosures 20, 21, 22, 23, 24, 25, 26, 27 or 28, wherein the gel content of the adhesive layer is 10% by mass or more and 85% by mass or less.

[0041] This disclosure 30 relates to adhesive tapes of disclosures 20, 21, 22, 23, 24, 25, 26, 27, 28 or 29, wherein the thickness of the adhesive layer is 5 μm or more and 200 μm or less.

[0042] This disclosure 31 relates to adhesive tapes of disclosures 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30, which have a substrate.

[0043] This disclosure 32 relates to the adhesive tape of this disclosure 31, wherein the substrate comprises at least one selected from nonwoven fabric, polyester film, polyimide film, polyamide film, polyetheretherketone film, polyphenylene ether film and polyphenylene sulfide film.

[0044] This disclosure 33 relates to adhesive tapes of disclosures 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31 or 32, wherein the overall thickness of the aforementioned adhesive tape is 50 μm or more and 200 μm or less.

[0045] This disclosure 34 relates to adhesive tapes of disclosures 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32 or 33, used for securing electronic device components or vehicle components.

[0046] This disclosure 35 relates to an adhesive composition comprising an acrylic copolymer and an organic solvent, wherein the acrylic copolymer has structural units derived from alkyl (meth)acrylates, structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds, and structural units derived from monomers containing polar functional groups. The structural units derived from alkyl (meth)acrylates include structural units of alkyl (meth)acrylates derived from alcohols having 1 or more and 4 or fewer carbon atoms. The proportion of the structural units derived from alkyl (meth)acrylates having 1 or more and 4 or fewer carbon atoms is 50% by mass or more and 100% by mass or less. The proportion of the structural units derived from alkyl (meth)acrylates in the acrylic copolymer is 50% by mass or more and 90% by mass or less. The proportion of the structural units derived from monomers containing polar functional groups in the acrylic copolymer is 3% by mass or more and 15% by mass or less. The weight-average molecular weight of the acrylic copolymer is 750,000 or more and less than 1,500,000.

[0047] This disclosure 36 relates to an adhesive composition of this disclosure 35, wherein the structural unit derived from alkyl (meth)acrylate comprises a structural unit of alkyl (meth)acrylate derived from an alcohol having 1 or more and 2 or less carbon atoms, and the content of the structural unit of alkyl (meth)acrylate derived from an alcohol having 1 or more and 2 or less carbon atoms is 10% by mass or more and 80% by mass or less.

[0048] The present invention will now be described in detail.

[0049] It should be noted that the adhesive tape of this disclosure 1 is also referred to as "the adhesive tape of this invention 1", and the adhesive tape of this disclosure 20 is also referred to as "the adhesive tape of this invention 2". In addition, matters shared by the adhesive tape of this invention 1 and the adhesive tape of this invention 2 are not specifically specified, or are described as "the adhesive tape of this invention".

[0050] The inventors investigated adjusting the shear storage modulus and loss tangent of the adhesive layer in an adhesive tape having an adhesive layer containing an acrylic copolymer to a specific range under high-temperature conditions. The results showed that an adhesive tape with excellent adhesion under high-temperature conditions could be obtained, thus completing the present invention 1.

[0051] Furthermore, the inventors investigated that by including a highly polar acrylic olefin copolymer with a specific composition in the adhesive layer of an adhesive tape, the cohesive strength of the adhesive layer at high temperatures can be improved. In addition, the inventors investigated that by including alkyl acrylates with fewer carbon atoms and monomers containing polar functional groups in a specific proportion as monomers constituting the acrylic olefin copolymer, the resulting acrylic olefin copolymer has a specific weight-average molecular weight. The results showed that the cohesive strength of the adhesive layer at high temperatures can be improved, resulting in an adhesive tape with excellent adhesion at high temperatures, thus completing Invention 2.

[0052] The adhesive tape of the present invention has an adhesive layer.

[0053] In the adhesive tape of the present invention, the lower limit of the shear storage modulus (G') of the adhesive layer at 150°C (hereinafter sometimes simply referred to as "shear storage modulus at 150°C"), measured by dynamic viscoelasticity measurement at a measurement frequency of 1 Hz, is 8.0 × 10⁻⁶. 4 Pa, with an upper limit of 3.0 × 10 5 Pa. By making the shear storage modulus of the above adhesive layer at 150°C 8.0 × 10⁻⁶. 4 With a pressure of Pa or higher, the cohesive force of the adhesive layer at high temperatures is increased, and the adhesive tape of the present invention exhibits excellent adhesion under high-temperature conditions.

[0054] The shear storage modulus of the above adhesive layer at 150°C is set to 3.0 × 10⁻⁶. 5 The adhesive layer is kept below Pa, thus preventing it from becoming too hard at high temperatures, resulting in excellent adhesive strength of the adhesive tape of the present invention at high temperatures. The preferred lower limit of the shear storage modulus of the adhesive layer at 150°C is 1.0 × 10⁻⁶. 5 Pa, preferably with an upper limit of 2.5 × 10 5 Pa, with a more preferred lower limit of 1.2 × 10 Pa. 5 Pa, more preferably an upper limit of 2.0 × 10 Pa. 5 Pa.

[0055] Furthermore, in the adhesive tape of the present invention 2, the preferred lower limit of the shear storage modulus of the adhesive layer at 150°C is 8.0 × 10⁻⁶. 4 Pa, preferably with an upper limit of 3.0 × 10 5 Pa. By making the shear storage modulus of the above adhesive layer at 150°C 8.0 × 10⁻⁶. 4 Pa or higher, thereby further improving the cohesive strength of the adhesive layer at high temperatures, and making the adhesive tape of the present invention 2 exhibit superior adhesion under high-temperature conditions. This is achieved by setting the shear storage modulus of the adhesive layer at 150°C to 3.0 × 10⁻⁶ Pa.5 The adhesive layer is kept below Pa, thus preventing it from becoming too hard at high temperatures, resulting in superior adhesive strength of the adhesive tape of the present invention 2 at high temperatures. A more preferred lower limit for the shear storage modulus of the adhesive layer at 150°C is 1.0 × 10⁻⁶. 5 Pa, more preferably an upper limit of 2.5 × 10 Pa. 5 Pa, the further preferred lower limit is 1.2 × 10 5 Pa, with a further preferred upper limit of 2.0 × 10⁻⁶. 5 Pa.

[0056] In the adhesive tape of the present invention 1, the lower limit of the loss tangent (tanδ) of the adhesive layer at 150°C (hereinafter sometimes simply referred to as "loss tangent at 150°C"), measured by dynamic viscoelasticity measurement at a measurement frequency of 1 Hz, is 0.10, and the upper limit is 0.40. By making the loss tangent of the adhesive layer at 150°C 0.10 or higher, the adhesive layer becomes soft and can easily adhere to the substrate. By making the loss tangent of the adhesive layer at 150°C 0.40 or lower, the cohesive force of the adhesive layer at high temperature is increased, and sufficient cohesive force for the adhesive layer to exert its adhesive force can be maintained even in high-temperature environments. Therefore, the adhesive tape of the present invention 1 exhibits excellent adhesive force at high-temperature environments. The preferred lower limit of the loss tangent of the adhesive layer at 150°C is 0.12, the preferred upper limit is 0.35, the more preferred lower limit is 0.14, and the more preferred upper limit is 0.30.

[0057] Furthermore, in the adhesive tape of the present invention 2, the preferred lower limit of the loss tangent at 150°C is 0.10, and the preferred upper limit is 0.40. By making the loss tangent of the adhesive layer at 150°C 0.10 or higher, the adhesive layer becomes more flexible and can more easily adhere to the substrate. By making the loss tangent of the adhesive layer at 150°C 0.40 or lower, the cohesive force of the adhesive layer at high temperature is further improved, and sufficient cohesive force for the adhesive layer to exert its adhesive force can be maintained even in high-temperature environments. Therefore, the adhesive tape of the present invention 2 exhibits superior adhesive force at high-temperature environments. The more preferred lower limit of the loss tangent of the adhesive layer at 150°C is 0.12, the more preferred upper limit is 0.35, the further preferred lower limit is 0.14, and the further preferred upper limit is 0.30.

[0058] The shear storage modulus of the adhesive layer at 150°C and the loss tangent (tanδ) of the adhesive layer at 150°C can be determined by dynamic viscoelasticity measurement.

[0059] That is, for the obtained adhesive layer, the dynamic viscoelastic spectrum is measured using a dynamic viscoelasticity measuring device (such as the "DVA-200" manufactured by IT Measurement & Control Co., Ltd.), under nitrogen atmosphere, shear direction, frequency 1 Hz, heating rate 5 °C / min, temperature range -100 °C to 200 °C, strain 0.08%, and the shear storage modulus of the above adhesive layer at 150 °C and the loss tangent (tanδ) of the above adhesive layer at 150 °C can be obtained.

[0060] It should be noted that when the thickness of the adhesive layer is less than 500 μm, an adhesive layer for testing is prepared by laminating adhesive layers in a manner that makes the thickness 500 μm or more, and dynamic viscoelasticity is measured.

[0061] Methods for adjusting the shear storage modulus of the adhesive layer at 150°C include: adjusting the polarity of the acrylic copolymer (methods for adjusting the proportion of alkyl methacrylates with 1 or more and 4 or fewer carbon atoms from the alcohol source, methods for adjusting the proportion of structural units derived from monomers containing polar functional groups); adjusting the molecular weight of the acrylic copolymer; and adjusting the type and content of the tackifying resin, crosslinking agent, and silane coupling agent (methods for adjusting the type and content of the tackifying resin, crosslinking agent, and silane coupling agent).

[0062] Methods for adjusting the loss tangent (tanδ) of the adhesive layer at 150°C include: adjusting the polarity of the acrylic copolymer (methods for adjusting the proportion of alkyl methacrylates with 1 or more and 4 or fewer carbon atoms from the alcohol source, methods for adjusting the proportion of structural units derived from monomers containing polar functional groups, etc.); adjusting the molecular weight of the acrylic copolymer; and adjusting the type and content of the tackifying resin, crosslinking agent, and silane coupling agent, etc.

[0063] In the adhesive tape of the present invention, the adhesive layer contains an acrylic copolymer.

[0064] The aforementioned acrylic copolymers preferably have structural units derived from alkyl (meth)acrylates.

[0065] It should be noted that in this specification, "(meth)acrylic acid" refers to acrylic acid or methacrylic acid.

[0066] In the adhesive tape of the present invention 2, the structural units derived from alkyl (meth)acrylate include structural units of alkyl (meth)acrylate derived from alcohols having 1 or more and 4 or less carbon atoms. Furthermore, in the adhesive tape of the present invention 1, the structural units derived from alkyl (meth)acrylate preferably include structural units of alkyl (meth)acrylate derived from alcohols having 1 or more and 4 or less carbon atoms. By making the structural units derived from alkyl (meth)acrylate have the structural units of alkyl (meth)acrylate derived from alcohols having 1 or more and 4 or less carbon atoms, the polarity of the acrylic copolymer becomes greater, thereby increasing the cohesive strength of the adhesive layer. As a result, the adhesive strength of the adhesive tape of the present invention is improved, particularly in maintaining sufficient cohesive strength for the adhesive layer to exert its adhesive force even at high temperatures, thus improving the adhesive strength of the adhesive tape of the present invention at high temperatures.

[0067] It should be noted that, in this specification, "alcohol-derived alkyl" refers to an alkyl group bonded to the oxygen atom of the ester bond in an alkyl (meth)acrylate.

[0068] In the adhesive tape of the present invention 2, the lower limit of the content of the structural units derived from alkyl (meth)acrylates, specifically those derived from alcohols and having 1 or more but less than 4 carbon atoms, is 50% by mass. Furthermore, in the adhesive tape of the present invention 1, the preferred lower limit of the content of the structural units derived from alkyl (meth)acrylates, specifically those derived from alcohols and having 1 or more but less than 4 carbon atoms, is 50% by mass. By ensuring that the content of the structural units derived from alcohols and having 1 or more but less than 4 carbon atoms is 50% by mass or more, the polarity of the acrylic copolymer increases, thereby increasing the cohesive force of the adhesive layer. As a result, the adhesive strength of the adhesive tape of the present invention is improved. In particular, sufficient cohesive force for the adhesive layer to exert its adhesive force can be maintained even at high temperatures, thus improving the adhesive strength of the adhesive tape of the present invention at high temperatures. In the adhesive tape of the present invention 2, the preferred lower limit of the content of the structural unit of (meth)acrylate alkyl ester derived from alcohol having 1 or more and 4 or less carbon atoms is 60% by mass, and a more preferred lower limit is 70% by mass. Furthermore, in the adhesive tape of the present invention 1, the preferred lower limit of the content of the structural unit of (meth)acrylate alkyl ester derived from alcohol having 1 or more and 4 or less carbon atoms is 60% by mass, and a more preferably lower limit is 70% by mass.

[0069] In the adhesive tape of the present invention, the maximum content of the structural unit of (meth)acrylate alkyl ester derived from alcohol having 1 or more and 4 or less carbon atoms can be 100% by mass, that is, the structural unit derived from (meth)acrylate alkyl ester can be composed only of the structural unit of (meth)acrylate alkyl ester derived from alcohol having 1 or more and 4 or less carbon atoms.

[0070] Alkyl methacrylates, where the alkyl group from which the alcohol originates has 1 or more but less than 4 carbon atoms, are examples of alkyl methacrylates obtained by dehydrating (meth)acrylic acid with an alkyl group having 1 or more but less than 4 carbon atoms in a linear or branched form. Specifically, examples include methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, and isobutyl methacrylate. From the viewpoint that the polarity of the aforementioned acrylic copolymers increases, alkyl methacrylates where the alkyl group from which the alcohol originates has 1 or more but less than 2 carbon atoms are preferred. That is, the structural unit derived from the alkyl methacrylate preferably includes a structural unit from an alkyl methacrylate where the alkyl group from the alcohol originates has 1 or more but less than 2 carbon atoms.

[0071] In the aforementioned structural units derived from alkyl (meth)acrylates, the preferred lower limit for the content of structural units derived from alcohol-derived alkyl groups having 1 or more and 2 or less carbon atoms is 10% by mass, and the preferred upper limit is 80% by mass. By making the content of structural units derived from alcohol-derived alkyl groups having 1 or more and 2 or less carbon atoms of alkyl (meth)acrylates 10% by mass or more, the polarity of the aforementioned acrylic copolymer becomes greater, thus further increasing the cohesive force of the aforementioned adhesive layer, resulting in further improvement in the adhesive strength of the adhesive tape of the present invention. In particular, since sufficient cohesive force for the adhesive layer to exert adhesive force can be maintained even at high temperatures, the adhesive strength of the adhesive tape of the present invention is improved at high temperatures. By making the content of structural units derived from alcohol-derived alkyl groups having 1 or more and 2 or less carbon atoms of alkyl (meth)acrylates 80% by mass or less, the glass transition temperature of the aforementioned acrylic copolymer (described later) can be easily adjusted to an appropriate range, further improving the adhesive strength of the adhesive tape of the present invention. The preferred lower limit for the content of the above-mentioned structural unit of alkyl (meth)acrylate derived from alcohol having 1 or more and 2 or less carbon atoms is 30% by mass, the preferred upper limit is 70% by mass, the further preferred lower limit is 45% by mass, and the further preferred upper limit is 60% by mass.

[0072] The structural units derived from (meth)acrylates may be structural units derived from (meth)acrylates other than those derived from alcohols, which have 1 or more and 4 or fewer carbon atoms in the alkyl group.

[0073] In the adhesive tape of the present invention 2, the lower limit of the content of the structural unit derived from (meth)acrylate in the aforementioned acrylic copolymer is 50% by mass, and the upper limit is 90% by mass. Furthermore, in the adhesive tape of the present invention 1, the preferred lower limit of the content of the structural unit derived from (meth)acrylate in the aforementioned acrylic copolymer is 50% by mass, and the preferred upper limit is 90% by mass. By keeping the content of the structural unit derived from (meth)acrylate within the aforementioned range, sufficient flexibility and cohesive strength for the adhesive layer to exert adhesive force can be achieved. In the adhesive tape of the present invention 2, the preferred lower limit of the content of the structural unit derived from (meth)acrylate is 60% by mass, the preferred upper limit is 80% by mass, the more preferred lower limit is 65% by mass, and the more preferred upper limit is 75% by mass. Furthermore, in the adhesive tape of the present invention 1, the more preferred lower limit of the content of the structural unit derived from (meth)acrylate is 60% by mass, the more preferred upper limit is 80% by mass, the further preferred lower limit is 65% by mass, and the further preferred upper limit is 75% by mass.

[0074] In the adhesive tape of the present invention 2, the acrylic copolymer has structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds. Furthermore, in the adhesive tape of the present invention 1, it is preferable that the acrylic copolymer has structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds. By having the acrylic copolymer have structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds, these structural units aggregate through interaction, forming a structure with pseudo-crosslinking points. By giving the acrylic copolymer such a structure, the adhesive layer exhibits hard properties like a crosslinked adhesive layer at low strain, and its holding power is improved. On the other hand, when peel stress is applied and the strain increases, the pseudo-crosslinks are broken, the molecules of the acrylic copolymer elongate, and therefore the adhesive layer exhibits highly flexible properties, resulting in improved adhesion. In other words, by having the acrylic copolymer have structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds, the adhesive strength and holding power of the adhesive layer are improved.

[0075] The aforementioned olefin copolymers with polymerizable unsaturated double bonds at both ends can have polymerizable unsaturated double bonds at one end or at both ends. From the viewpoint of easily forming an appropriate number of pseudo-crosslinks, olefin copolymers with polymerizable unsaturated double bonds at one end are preferred.

[0076] Examples of olefin copolymers with polymerizable unsaturated double bonds at the ends include ethylene-butene copolymers, ethylene-propylene copolymers, ethylene polymers, propylene polymers, and butene polymers, which have groups with polymerizable unsaturated double bonds at one or both ends.

[0077] It should be noted that these olefin copolymers with polymerizable unsaturated double bonds at the ends can be used alone or in combination of two or more.

[0078] Examples of groups possessing polymerizable unsaturated double bonds include (meth)acryloyl, vinyl ether, and styrene groups. Among these, (meth)acryloyl is preferred from the perspective of excellent copolymerization properties with the aforementioned alkyl (meth)acrylates.

[0079] It should be noted that in this specification, "(meth)acryloyl" refers to acryloyl or methacryloyl.

[0080] Examples of olefin copolymers with (meth)acryloyl groups at the ends include: ethylene macromonomers with (meth)acryloyl groups at a single end, propylene macromonomers with (meth)acryloyl groups at a single end, ethylene-butene macromonomers with (meth)acryloyl groups at a single end, and ethylene-propylene macromonomers with (meth)acryloyl groups at a single end. Among these, ethylene-butene macromonomers with (meth)acryloyl groups at a single end and ethylene-propylene macromonomers with (meth)acryloyl groups at a single end are preferred from the perspective of easily satisfying the glass transition temperature described later and further improving the adhesive strength of the adhesive layer.

[0081] It should be noted that, in this specification, "macromonomer" refers to a monomer with a weight-average molecular weight of 1,000 or more but less than 100,000 that has functional groups capable of polymerization.

[0082] In the aforementioned acrylic copolymers, the preferred lower limit for the content of structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds is 5% by mass, and the preferred upper limit is 50% by mass. By ensuring that the content of the structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds is 5% by mass or more, the acrylic copolymer forms an appropriate amount of pseudo-crosslinks, further improving the adhesive strength and holding power of the adhesive layer. By ensuring that the content of the structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds is 50% by mass or less, cohesive failure of the adhesive layer can be further suppressed. The more preferred lower limit for the content of the structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds is 8% by mass, the more preferred lower limit is 10% by mass, the more preferred upper limit is 30% by mass, the more preferred upper limit is 27% by mass, and the particularly preferred upper limit is 25% by mass.

[0083] In the adhesive tape of the present invention 2, the aforementioned acrylic copolymer has structural units derived from monomers containing polar functional groups. Furthermore, in the adhesive tape of the present invention 1, it is preferable that the aforementioned acrylic copolymer has structural units derived from monomers containing polar functional groups. By giving the aforementioned acrylic copolymer structural units derived from monomers containing polar functional groups, the polarity of the acrylic copolymer increases, thereby increasing the cohesive force of the adhesive layer, resulting in improved adhesive force of the adhesive tape of the present invention. In particular, sufficient cohesive force for the adhesive layer to exert its adhesive force can be maintained even at high temperatures, thus improving the adhesive force of the adhesive tape of the present invention at high temperatures. Furthermore, when the adhesive layer contains the crosslinking agent described later, the aforementioned acrylic copolymer is crosslinked by the crosslinking agent, thereby improving the adhesive force and holding power of the adhesive layer. By adjusting the degree of crosslinking at this time, the gel fraction of the adhesive layer described later can be adjusted to an appropriate range.

[0084] Examples of monomers containing polar functional groups include, for instance, monomers containing carboxyl groups, monomers containing hydroxyl groups, monomers containing amide groups, and monomers containing amino groups. From the viewpoint of further improving the adhesive strength and holding power of the adhesive layer, the monomers containing polar functional groups preferably include at least one selected from monomers containing carboxyl groups and monomers containing hydroxyl groups.

[0085] It should be noted that these monomers containing polar functional groups can be used alone or in combination of two or more.

[0086] Examples of the aforementioned carboxyl-containing monomers include: (meth)acrylic acid, (meth)acryloylacetic acid, (meth)acryloylpropionic acid, (meth)acryloylbutyric acid, (meth)acryloylvaleric acid, crotonic acid, maleic acid, fumaric acid, citraconic acid, medoconic acid, itaconic acid, and other unsaturated carboxylic acids.

[0087] Examples of hydroxyl-containing monomers include 4-hydroxybutyl methacrylate and 2-hydroxyethyl methacrylate.

[0088] Examples of monomers containing amide groups include N-vinyl-2-pyrrolidone, (meth)acrylamide, N,N-dimethyl (meth)acrylamide, and N-isopropyl (meth)acrylamide.

[0089] Examples of amino-containing monomers include (meth)acryloylmorpholine, 2-dimethylaminoethyl (meth)acrylate, and 2-diethylaminoethyl (meth)acrylate.

[0090] In the adhesive tape of the present invention 2, the content of the structural units derived from monomers containing polar functional groups in the aforementioned acrylic copolymer is at least 3% by mass and at most 15% by mass. Furthermore, in the adhesive tape of the present invention 1, the preferred content of the structural units derived from monomers containing polar functional groups in the aforementioned acrylic copolymer is at least 3% by mass and at most 15% by mass. By making the content of the structural units derived from monomers containing polar functional groups at 3% by mass or more, the polarity of the aforementioned acrylic copolymer increases, thereby increasing the cohesive force of the adhesive layer, resulting in improved adhesive strength of the adhesive tape of the present invention. In particular, sufficient cohesive force for the adhesive layer to exert its adhesive force can be maintained even at high temperatures, thus improving the adhesive strength of the adhesive tape of the present invention at high temperatures. By making the content of the structural units derived from monomers containing polar functional groups at 15% by mass or less, the adhesive layer can be prevented from becoming too hard, thus improving the adhesive strength of the adhesive tape of the present invention. In the adhesive tape of the present invention 2, the preferred lower limit of the content ratio of the structural unit derived from the monomer containing polar functional groups is 4 by mass, the preferred upper limit is 10 by mass, the more preferred lower limit is 5 by mass, and the more preferred upper limit is 7 by mass. Furthermore, in the adhesive tape of the present invention 1, the preferred lower limit of the content ratio of the structural unit derived from the monomer containing polar functional groups is 4 by mass, the more preferred upper limit is 10 by mass, the further preferred lower limit is 5 by mass, and the further preferred upper limit is 7 by mass.

[0091] The aforementioned acrylic copolymers may have structural units derived from other monomers, except for the structural units derived from alkyl (meth)acrylates, the structural units derived from olefin copolymers with polymerizable unsaturated double bonds at the ends, and the structural units derived from monomers containing polar functional groups.

[0092] The glass transition temperature (Tg) of the aforementioned acrylic copolymer is preferably in the range of -100°C to 200°C, and more preferably -20°C. By setting the glass transition temperature of the aforementioned acrylic copolymer to below -20°C, the molecules of the acrylic copolymer become easier to stretch, thereby further improving the adhesive strength of the adhesive layer. A further preferred upper limit for the glass transition temperature of the aforementioned acrylic copolymer is -30°C, and a particularly preferred upper limit is -35°C. Furthermore, when the adhesive layer contains multiple types of the aforementioned acrylic copolymer, it is preferable that the glass transition temperature of all of the aforementioned acrylic copolymers is below -20°C.

[0093] It should be noted that the glass transition temperature of the aforementioned acrylic copolymer can be determined by differential scanning calorimetry (DSC). More specifically, under a nitrogen atmosphere (nitrogen flow rate 50 mL / min), using a differential scanning calorimeter (Seiko Instruments, "220C", etc.), and following the method according to JIS K6240:2011, the glass transition temperature of the aforementioned acrylic copolymer can be determined at a measurement temperature of -100℃ to 200℃ and a heating rate of 10℃ / min.

[0094] The glass transition temperature of the above-mentioned acrylic copolymer can be adjusted by changing the type and content of the monomers used as raw materials for the above-mentioned acrylic copolymer.

[0095] In the adhesive tape of the present invention 2, the weight-average molecular weight (Mw) of the aforementioned acrylic copolymer is 750,000 or more and less than 1,500,000. Furthermore, in the adhesive tape of the present invention 1, the weight-average molecular weight (Mw) of the aforementioned acrylic copolymer is preferably 750,000 or more and less than 1,500,000. By making the weight-average molecular weight of the aforementioned acrylic copolymer 750,000 or more, the cohesive force of the adhesive layer is increased, thereby improving the adhesive force of the adhesive tape of the present invention. In particular, sufficient cohesive force for the adhesive layer to exert its adhesive force can be maintained even under high-temperature environments, thus improving the adhesive force of the adhesive tape of the present invention under high-temperature environments. By making the weight-average molecular weight of the aforementioned acrylic copolymer less than 1,500,000, the adhesive layer can be prevented from becoming too hard, thus improving the initial adhesive force of the adhesive layer. In the adhesive tape of the present invention 2, the preferred lower limit of the weight-average molecular weight of the aforementioned acrylic copolymer is 800,000, the preferred upper limit is 1,400,000, the more preferred lower limit is 900,000, and the more preferred upper limit is 1,200,000. Furthermore, in the adhesive tape of the present invention 1, the weight-average molecular weight of the above-mentioned acrylic copolymer is more preferably a lower limit of 800,000, more preferably an upper limit of 1,400,000, further preferably a lower limit of 900,000, and further preferably an upper limit of 1,200,000.

[0096] The preferred lower limit for the ratio of weight-average molecular weight (Mw) to number-average molecular weight (Mn) of the aforementioned acrylic copolymer (polydispersity index: Mw / Mn) is 1.0, and the preferred upper limit is 6.0. By keeping the polydispersity index of the aforementioned acrylic copolymer within the above range, the adhesive strength and holding power of the aforementioned adhesive layer are further improved. A more preferred lower limit for the polydispersity index of the aforementioned acrylic copolymer is 1.2, a more preferred upper limit is 5.0, a further preferred lower limit is 1.5, and a further preferred upper limit is 4.5.

[0097] In this specification, weight-average molecular weight (Mw) and number-average molecular weight (Mn) refer to the weight-average molecular weight converted from standard polystyrene as determined by gel permeation chromatography (GPC). Specifically, the acrylic copolymer is diluted 50-fold with tetrahydrofuran (THF), and the diluted solution is filtered using a filter (material: polytetrafluoroethylene, pore size: 0.2 μm). The resulting filtrate is fed into a gel permeation chromatograph (Waters Corporation, "2690 Separations Model", etc.), and GPC is performed at a sample flow rate of 1 mL / min and a column temperature of 40°C to determine the polystyrene-converted molecular weight of the acrylic copolymer, thereby calculating the weight-average molecular weight (Mw) and number-average molecular weight (Mn). For example, a GPC KF-806L (Showa Denko Corporation) can be used as the column, and a differential refractometer can be used as the detector. Furthermore, the polydispersity index (Mw / Mn) can be obtained by using the obtained weight-average molecular weight (Mw) and number-average molecular weight (Mn).

[0098] Methods for adjusting the weight-average molecular weight of the aforementioned acrylic copolymers include, for example, changing the polymerization temperature, changing the polymerization time, changing the type of solvent used in the polymerization, changing the type of monomer, changing the concentration of the monomer, and adding a chain transfer agent.

[0099] In the aforementioned adhesive layer, the preferred lower limit for the content of the aforementioned acrylic copolymer is 70% by mass. By ensuring that the content of the aforementioned acrylic copolymer is 70% by mass or more, the adhesive strength of the adhesive tape of the present invention is further improved.

[0100] In addition, the content of the above-mentioned acrylic copolymer can be 100% by mass, but from the viewpoint that the cohesive force of the above-mentioned adhesive layer can be further improved by including the silane coupling agent, crosslinking agent and the like described later in the adhesive layer, the preferred upper limit is 99% by mass, and the more preferred upper limit is 98% by mass.

[0101] As a polymerization method for synthesizing the above-mentioned (meth)acrylic acid copolymers, conventionally known methods can be used, which involve subjecting a mixture of monomers used as raw materials to a free radical reaction in the presence of a polymerization initiator. Examples include solution polymerization (boiling point polymerization or isothermal polymerization), emulsion polymerization, suspension polymerization, and bulk polymerization. Among these, solution polymerization is preferred from the perspective of ease of synthesis.

[0102] When solution polymerization is used as the polymerization method described above, examples of reaction solvents include ethyl acetate, toluene, methyl ethyl ketone, methyl sulfoxide, ethanol, acetone, and diethyl ether. These reaction solvents can be used alone or in combination of two or more.

[0103] Examples of polymerization initiators include organic peroxides and azo compounds.

[0104] Examples of the aforementioned organic peroxides include: 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, tert-hexyl peroxypentanoate, tert-butyl peroxypentanoate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, and tert-butyl peroxylaurate.

[0105] Examples of the aforementioned azo compounds include azobisisobutyronitrile and azobiscyclohexaneformitrile.

[0106] These polymerization initiators can be used alone or in combination of two or more.

[0107] The adhesive layer described above preferably further contains a silane coupling agent. By containing a silane coupling agent in the adhesive layer, chemical bonds are formed between the adhesive and the adhesive layer through the condensation reaction of hydroxyl groups and silanol groups on the surface of the substrate. In particular, sufficient interfacial interactions for the adhesive layer to exert adhesive force are maintained even at high temperatures. As a result, the adhesive strength of the adhesive tape of the present invention is further improved at high temperatures. The effect of improved adhesive strength due to the presence of the silane coupling agent is particularly significant when the substrate is a glass or other substrate with a large number of hydroxyl groups on its surface.

[0108] From the viewpoint of wanting to form chemical bonds with the aforementioned acrylic copolymers, the silane coupling agent preferably has a reactive site for forming chemical bonds with the aforementioned acrylic copolymers. Examples of such reactive sites include epoxy groups, functional groups having carbon-carbon double bonds (vinyl, (meth)acryloyl, etc.), amino groups, and mercapto groups. Among these, epoxy groups are preferred from the viewpoint of excellent reactivity. It should be noted that, in this specification, the carbon-carbon double bond contained in the aromatic ring is not included in the carbon-carbon double bond of the aforementioned functional groups having carbon-carbon double bonds.

[0109] Examples of silane coupling agents having the aforementioned reactive sites include: vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, 2-(3,4- Examples of suitable adhesives include (2-aminoethyl)3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethylmethoxysilane, N-(2-aminoethyl)3-aminopropyltriethoxysilane, N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, mercaptobutyltrimethoxysilane, and γ-mercaptopropylmethyldimethoxysilane. Among these, γ-epoxypropyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane are preferred from the viewpoint that the adhesive strength of the resulting adhesive tape is more easily improved.

[0110] It should be noted that these silane coupling agents can be used alone or in combination of two or more.

[0111] The preferred lower limit for the content of the silane coupling agent relative to 100 parts by weight of the aforementioned acrylic copolymer is 0.1 parts by weight, and the preferred upper limit is 3.0 parts by weight. By making the content of the silane coupling agent 0.1 parts by weight or more, chemical bonds are formed between the adhered material and the adhesive layer, and in particular, sufficient interfacial interaction for the adhesive layer to exert adhesive force is maintained even at high temperatures, thus further improving the adhesive strength of the adhesive tape of the present invention at high temperatures. By making the content of the silane coupling agent 3.0 parts by weight or less, the adhesive layer can be prevented from becoming too hard, thus further improving the adhesive strength of the adhesive tape of the present invention. The more preferred lower limit for the content of the silane coupling agent is 0.3 parts by weight, the more preferred upper limit is 2.0 parts by weight, the further preferred lower limit is 0.5 parts by weight, and the further preferred upper limit is 1.0 parts by weight.

[0112] The adhesive layer preferably further contains a crosslinking agent. By including a crosslinking agent in the adhesive layer, a crosslinked structure is formed in which the acrylic copolymer is crosslinked by the crosslinking agent, thus further increasing the cohesive strength of the adhesive layer. As a result, the adhesive strength of the adhesive tape of the present invention is further improved. In particular, sufficient cohesive strength for the adhesive layer to exert its adhesive force can be maintained even at high temperatures, thus further improving the adhesive strength of the adhesive tape of the present invention at high temperatures. By adjusting the degree of crosslinking at this time, the gel fraction of the adhesive layer, described later, can be adjusted to an appropriate range.

[0113] Examples of crosslinking agents include epoxy-based crosslinking agents and isocyanate-based crosslinking agents. Among these, isocyanate-based crosslinking agents are preferred from the perspective of easily adjusting the gel fraction of the adhesive layer (described later) to an appropriate range and further improving the adhesive strength and holding power of the adhesive tape of the present invention.

[0114] Relative to 100 parts by weight of the aforementioned acrylic copolymer, the preferred lower limit of the crosslinking agent content is 0.05 parts by weight, and the preferred upper limit is 5.0 parts by weight. By keeping the crosslinking agent content within the above range, the gel fraction of the adhesive layer described later can be easily adjusted to an appropriate range, further improving the adhesive strength and holding power of the adhesive tape. A more preferred lower limit of the crosslinking agent content is 0.1 parts by weight, and a more preferred upper limit is 3.0 parts by weight.

[0115] The adhesive layer described above may further contain a tackifying resin. By including a tackifying resin in the adhesive layer, the adhesive strength of the adhesive tape of the present invention is further improved.

[0116] Examples of tackifying resins include terpene phenolic resins, rosin-based resins, xylene-based resins, terpene-based resins, and petroleum-based resins. From the viewpoint of higher polarity and further enhanced interaction between the adhesive layer and the adherend, the tackifying resin is preferably selected from at least one of terpene phenolic resins, rosin-based resins, and xylene-based resins.

[0117] It should be noted that these tackifying resins can be used alone or in combination of two or more.

[0118] Examples of the aforementioned terpene phenolic resins include YS Polyster G150 and YS Polyster G125 (both manufactured by Yasuhara Chemical Co., Ltd.).

[0119] Examples of the aforementioned rosin-based resins include Super Ester A-125 (manufactured by Arakawa Chemical Industry Co., Ltd.).

[0120] Examples of xylene-based resins include GHP-125 and GHP-150 (both manufactured by Fudow Corporation).

[0121] The preferred upper limit for the content of the tackifying resin is 20 parts by mass relative to 100 parts by mass of the aforementioned acrylic copolymer. By keeping the content of the tackifying resin at 20 parts by mass or less, it is possible to prevent a decrease in adhesive strength due to the exudation of low molecular weight components under high temperature conditions. A more preferred upper limit for the content of the tackifying resin is 10 parts by mass.

[0122] The aforementioned adhesive layer may contain, as needed, previously known particles and additives such as inorganic microparticles, conductive microparticles, antioxidants, foaming agents, organic fillers, and inorganic fillers.

[0123] The preferred lower limit for the gel content of the adhesive layer is 10% by mass, and the preferred upper limit is 85% by mass. By making the gel content of the adhesive layer 10% by mass or more, the cohesive force of the adhesive layer is further improved, resulting in superior adhesive strength of the adhesive tape of the present invention. In particular, sufficient cohesive force for the adhesive layer to exert its adhesive force can be maintained even at high temperatures, thus the adhesive strength of the adhesive tape of the present invention is superior at high temperatures. By making the gel content of the adhesive layer 85% by mass or less, the adhesive layer can be prevented from becoming too hard, thus further improving the adhesive strength of the adhesive tape. The preferred lower limit for the gel content of the adhesive layer is 20% by mass, the preferred upper limit is 65% by mass, the more preferred lower limit is 30% by mass, and the more preferred upper limit is 50% by mass.

[0124] It should be noted that the gel content of the above-mentioned adhesive layer can be determined by the following methods.

[0125] That is, test pieces were made by cutting the adhesive tape into flat rectangular shapes of 50mm × 100mm. The test pieces were immersed in tetrahydrofuran (THF) at 23°C for 24 hours, then removed from the tetrahydrofuran and dried at 110°C for 1 hour. The mass of the dried test pieces was measured, and the gel fraction was calculated using the following formula (1). It should be noted that no release film for protecting the adhesive layer was laminated on the test pieces. In addition, when the adhesive tape does not have a substrate, W0 = 0.

[0126] Gel fraction (mass%) = 100 × (W2 - W0) / (W1 - W0) (1)

[0127] (W0: quality of the substrate, W1: quality of the test piece before impregnation, W2: quality of the test piece after impregnation and drying)

[0128] Methods for adjusting the gel fraction of the adhesive layer include: adjusting the proportion of structural units derived from monomers containing polar functional groups in the acrylic copolymer; adjusting the type and content of the tackifying resin and the crosslinking agent; etc.

[0129] The preferred lower limit for the thickness of the adhesive layer is 5 μm, and the preferred upper limit is 200 μm. By making the thickness of the adhesive layer 5 μm or more, the adhesive force of the adhesive tape of the present invention is further improved. By making the thickness of the adhesive layer 200 μm or less, deformation of the adhesive tape of the present invention is suppressed, and the adhesive force at high temperature is further improved. The more preferred lower limit for the thickness of the adhesive layer is 10 μm, the more preferred upper limit is 100 μm, the even more preferred lower limit is 25 μm, and the even more preferred upper limit is 50 μm.

[0130] It should be noted that, in this instruction manual, the thickness can be measured using a dial thickness gauge (Mitutoyo, "ABS Digimatic Indicator", etc.).

[0131] The adhesive tape of the present invention can be an unsupported type without a substrate or a supported type with a substrate. Preferably, the adhesive tape of the present invention has a substrate. By including a substrate in the adhesive tape of the present invention, operability is improved.

[0132] When the adhesive tape of the present invention has a substrate, it can be a single-sided adhesive tape with the adhesive layer on one side of the substrate, or a double-sided adhesive tape with the adhesive layer on both sides of the substrate. From an operability point of view, a double-sided adhesive tape with the adhesive layer on both sides of the substrate is preferred.

[0133] Examples of substrates mentioned above include nonwoven fabrics and film-like substrates.

[0134] Examples of substrates for the aforementioned films include: polyester (PE) films, polyimide (PI) films, polyamide (PA) films, polyether ether ketone (PEEK) films, polyphenylene ether (PPE) films, polyphenylene sulfide (PPS) films, and polyethylene terephthalate (PET) films.

[0135] From the viewpoint of heat resistance, the above-mentioned substrate is preferably selected from at least one of nonwoven fabric, polyester film, polyimide film, polyamide film, polyetheretherketone film, polyphenylene ether film and polyphenylene sulfide film.

[0136] The preferred lower limit for the thickness of the aforementioned substrate is 10 μm, and the preferred upper limit is 150 μm. By making the thickness of the aforementioned substrate 10 μm or more, the aforementioned adhesive tape has a moderate stiffness, and its operability becomes better. By making the thickness of the aforementioned substrate 150 μm or less, the adhesive force of the adhesive tape of the present invention is further improved. The more preferred lower limit for the thickness of the aforementioned substrate is 20 μm, the more preferred upper limit is 100 μm, the even more preferred lower limit is 40 μm, and the even more preferred upper limit is 75 μm.

[0137] The adhesive tape of the present invention may further have other layers without compromising the effects of the present invention.

[0138] The method for manufacturing the adhesive tape of the present invention is not particularly limited, and conventionally known methods can be used. For example, firstly, the above-mentioned alkyl methacrylate, the above-mentioned monomer containing polar functional groups, the above-mentioned olefin copolymer with polymerizable unsaturated double bonds at the ends, and other monomers as needed are copolymerized by conventional methods to obtain the above-mentioned acrylic copolymer. Next, the obtained acrylic copolymer is compounded with a silane coupling agent, crosslinking agent, tackifying resin, and other additives as needed to obtain an adhesive solution. This adhesive solution is applied to the release treatment surface of a film that has undergone a release treatment and then dried, thereby enabling manufacturing. Alternatively, the adhesive tape manufactured by the above method can be formed into an adhesive layer and bonded to a substrate to form a support-type adhesive tape.

[0139] The preferred lower limit of the overall thickness of the adhesive tape of the present invention is 50 μm, and the preferred upper limit is 200 μm. By making the overall thickness of the adhesive tape of the present invention 50 μm or more, the adhesive force of the adhesive tape of the present invention is further improved. By making the overall thickness of the adhesive tape of the present invention 200 μm or less, deformation of the adhesive tape of the present invention is suppressed, and the adhesive force at high temperature is further improved. The more preferred lower limit of the overall thickness of the adhesive tape of the present invention is 75 μm, the more preferred upper limit is 175 μm, the more preferred lower limit is 100 μm, and the more preferred upper limit is 150 μm.

[0140] The adhesive tape of this invention has no particularly limited application. Because it exhibits excellent adhesion even at high temperatures, it is suitable for fixing electronic device components or automotive components. Specifically, it is suitable for fixing, for example, covers protecting the surfaces of electronic devices, battery packs, fuel cell cells, automotive panels, and automotive exterior components.

[0141] The adhesive layer in the adhesive tape of the present invention can be obtained by using an adhesive composition.

[0142] The following adhesive composition is also part of the present invention, wherein the adhesive composition contains an acrylic copolymer and an organic solvent, wherein the acrylic copolymer has structural units derived from alkyl (meth)acrylates, structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds, and structural units derived from monomers containing polar functional groups, wherein the structural units derived from alkyl (meth)acrylates include structural units of alkyl (meth)acrylates with 1 or more and 4 or less carbon atoms derived from alcohols, wherein the content of the structural units of alkyl (meth)acrylates with 1 or more and 4 or less carbon atoms derived from alcohols is 50% by mass or more and 100% by mass or less, wherein the content of the structural units derived from alkyl (meth)acrylates in the acrylic copolymer is 50% by mass or more and 90% by mass or less, wherein the content of the structural units derived from monomers containing polar functional groups in the acrylic copolymer is 3% by mass or more and 15% by mass or less, and wherein the weight average molecular weight of the acrylic copolymer is 750,000 or more and less than 1,500,000.

[0143] The acrylic copolymer used in the adhesive composition of the present invention is the same as the acrylic copolymer used in the adhesive layer of the adhesive tape of the present invention 2.

[0144] The adhesive composition of the present invention contains an organic solvent. By containing an organic solvent, the adhesive composition of the present invention can be easily applied.

[0145] Examples of organic solvents mentioned above include benzene, toluene, xylene, tetrahydronaphthalene, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, and isoamyl acetate.

[0146] The adhesive composition of the present invention preferably further contains a silane coupling agent.

[0147] The silane coupling agent described above is, for example, the same silane coupling agent used in the adhesive layer of the adhesive tape of the present invention.

[0148] The adhesive composition of the present invention preferably further contains a crosslinking agent.

[0149] The crosslinking agent described above may be, for example, the same crosslinking agent used in the adhesive layer of the adhesive tape of the present invention.

[0150] The adhesive composition of the present invention may further contain a tackifying resin.

[0151] The tackifying resin described above may be, for example, the same tackifying resin used in the adhesive layer of the adhesive tape of the present invention.

[0152] The adhesive composition of the present invention may contain, as needed, conventionally known microparticles and additives such as inorganic microparticles, conductive microparticles, antioxidants, foaming agents, organic fillers, and inorganic fillers.

[0153] Invention Effects

[0154] According to the present invention, an adhesive tape with excellent adhesion under high-temperature conditions can be provided. Furthermore, according to the present invention, an adhesive composition with excellent adhesion under high-temperature conditions can be provided. Detailed Implementation

[0155] The present invention will be described in more detail below with examples, but the present invention is not limited to these examples.

[0156] (Synthesis of acrylic copolymers A to X)

[0157] Ethyl acetate and the monomers shown in Table 1 were added to a reactor equipped with a thermometer, stirrer, and condenser, and the reactor was heated to initiate reflux. Next, 0.01 parts by mass of 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane as a polymerization initiator were added to the reactor, and polymerization was initiated under reflux. Then, 0.01 parts by mass of 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane were added one and two hours after the start of polymerization, respectively. Further, 0.05 parts by mass of tert-hexyl peroxypentanoate was added four hours after the start of polymerization, and the polymerization reaction continued. The polymerization reaction was then carried out for a total of 8 hours from the start of polymerization, yielding an ethyl acetate solution containing acrylic copolymers A to X. It should be noted that the molecular weight of each acrylic copolymer was adjusted by increasing or decreasing the amount of ethyl acetate to control the reaction solids composition.

[0158] In addition, the obtained acrylic copolymers were diluted 50-fold with tetrahydrofuran (THF), and the diluted solutions were filtered through a filter (material: polytetrafluoroethylene, pore size: 0.2 μm). 20 μL of the filtrate was fed into a gel permeation chromatograph (Waters Corporation, “2690 Separations Model”) and GPC was performed at a sample flow rate of 1 mL / min and a column temperature of 40 °C to determine the polystyrene-converted molecular weight of the acrylic copolymers. The weight-average molecular weight (Mw) and number-average molecular weight (Mn) were calculated, and the polydispersity index (Mw / Mn) was obtained. A GPC KF-806L column (Showa Denko Corporation) was used as the column, and a differential refractometer was used as the detector. The results are shown in Table 1.

[0159] The structural unit units shown in Table 1 are described below.

[0160] ·BA: n-Butyl acrylate

[0161] MA: Methyl acrylate

[0162] ·2EHA: 2-Ethylhexyl acrylate

[0163] •EBm: Ethylene-butene macromonomer (an olefin polymer with a single methacryloyl group at one end, manufactured by Kraton Polymers Japan, "HPVM-L1253", weight average molecular weight 7000)

[0164] • AAc: Acrylic acid

[0165] 4HBA: 4-Hydroxybutyl acrylate

[0166] [Table 1]

[0167]

[0168] (Examples 1-37, 39, 40, and Comparative Examples 1-9)

[0169] (1) Preparation of adhesive composition and adhesive tape

[0170] The components shown in Tables 2-5 were added to the ethyl acetate solution of the acrylic copolymer shown in Table 1 to obtain a solution containing the adhesive composition. Further, the solution containing the adhesive composition was thoroughly stirred to obtain an adhesive solution.

[0171] The obtained adhesive solution was applied to the release-treated surface of a 50 μm thick polyethylene terephthalate (PET) film that had undergone release treatment on one side. The film was dried at 110°C for 5 minutes to create a laminate with adhesive layers of the thicknesses shown in Tables 2-5 on the release-treated surface of the PET film. Substrates as shown in Tables 2-5 were prepared, and the resulting laminate was bonded to one side of the substrate with the adhesive layer facing the substrate. Furthermore, the same laminate was bonded to the other side of the substrate with the adhesive layer facing the substrate, and cured at 40°C for 48 hours, thereby obtaining an adhesive tape with adhesive layers of the same composition and thickness on both sides of the substrate.

[0172] (2) Gel fraction of adhesive layer

[0173] The obtained adhesive tape was cut into 50mm × 100mm rectangular shapes to prepare test pieces. The test pieces were immersed in tetrahydrofuran (THF) at 23°C for 24 hours, then removed from the THF and dried at 110°C for 1 hour. The mass of the dried test pieces was determined, and the gel fraction was calculated using the following formula (1). It should be noted that no release film for protecting the adhesive layer was laminated on the test pieces. The results are shown in Tables 2–5.

[0174] Gel fraction (mass%) = 100 × (W2 - W0) / (W1 - W0) (1)

[0175] (W0: quality of the substrate, W1: quality of the test piece before impregnation, W2: quality of the test piece after impregnation and drying)

[0176] (3) Shear storage modulus of adhesive layer at 150°C and loss tangent of adhesive layer at 150°C

[0177] In the above-mentioned "(1) Fabrication of Adhesive Tape", the adhesive layers of the fabricated laminates were overlapped to create a test sample consisting only of an adhesive layer with a thickness of 500 μm. For the obtained test sample, dynamic viscoelasticity was measured using a dynamic viscoelasticity measuring device (IT Measurement & Control Co., Ltd., "DVA-200") under nitrogen atmosphere, in the shear direction, at a frequency of 1 Hz, a heating rate of 5 °C / min, a temperature range of -100 °C to 200 °C, and a strain of 0.08%. The dynamic viscoelastic spectrum was measured, thereby obtaining the shear storage modulus (Pa) of the adhesive layer at 150 °C and the loss tangent of the adhesive layer at 150 °C. The results are shown in Tables 2-5.

[0178] (Example 38)

[0179] (1) Preparation of adhesive composition and adhesive tape

[0180] The components shown in Table 4 were added to the ethyl acetate solution of the acrylic copolymer K shown in Table 1 to obtain a solution containing the adhesive composition. Further, the solution containing the adhesive composition was thoroughly stirred to obtain an adhesive solution.

[0181] Using the obtained adhesive solution, a laminate with an adhesive layer of 100 μm thickness was prepared by the same method as in Examples 1-37, 39, 40 and Comparative Examples 1-9. Then, a PET film with a thickness of 50 μm that had been demolded was overlapped on the adhesive layer of the prepared laminate with the demolded surfaces facing each other, thereby obtaining an adhesive tape without a substrate.

[0182] (2) Gel fraction of adhesive layer

[0183] The gel fraction (mass %) of the adhesive layer was obtained using the same method as in Examples 1-37, 39, 40 and Comparative Examples 1-9. It should be noted that the calculation of the gel fraction of the adhesive layer was performed with W0 = 0 in the above formula (1). The results are shown in Table 4.

[0184] (3) Shear storage modulus of adhesive layer at 150°C and loss tangent of adhesive layer at 150°C

[0185] The shear storage modulus (Pa) of the adhesive layer at 150°C and the loss tangent of the adhesive layer at 150°C were obtained using the same method as in Examples 1-37, 39, 40 and Comparative Examples 1-9. The results are shown in Table 4.

[0186] <Evaluation>

[0187] The adhesive tapes obtained in the examples and comparative examples were evaluated as follows. The results are shown in Tables 2 to 5.

[0188] (Adhesive strength under high temperature conditions)

[0189] The obtained adhesive tape was cut into 25mm × 50mm rectangular shapes to prepare test pieces. Next, one release PET film of the test piece was peeled off and bonded to a 0.1mm thick SUS304 board (SUS304 board cleaned with ethanol and then dry-rubbed) by applying a 2kg hand roller at a speed of 300mm / min once. Then, the other release PET film was peeled off and bonded to a 0.1mm thick SUS304 board (SUS304 board cleaned with ethanol and then dry-rubbed) by applying a 2kg hand roller at a speed of 300mm / min once. The samples were then left to stand at 23°C for 24 hours to obtain the test samples. For the obtained test samples, according to JIS K6854-3:1999, a tensile testing machine (A&D Company, “RTI-1310”) was used to conduct a T-peel test at 100°C and a peel speed of 10 mm / min. The SUS304 board (the side to be tested) was peeled off from the adhesive tape of the test sample in the up-down direction, and the T-peel force on SUS at 100°C was measured.

[0190] The following conditions are marked as follows: ◎ represents a T-peel force of 20 N / 25 mm or more against SUS at 100 °C; ○ represents a T-peel force of 15 N / 25 mm or more but less than 20 N / 25 mm; △ represents a T-peel force of 10 N / 25 mm or more but less than 15 N / 25 mm; and × represents a T-peel force of less than 10 N / 25 mm. This is used to evaluate the adhesive strength of the tape under high temperature conditions.

[0191] The substrates shown in Tables 2-5 are as follows.

[0192] • PEN membrane: Polyethylene naphthalate membrane (manufactured by Teijin Corporation, "Teonex")

[0193] • PI film: Polyimide film (manufactured by DuPont-Toray, "Kapton")

[0194] • PEEK film: Polyetheretherketone film (manufactured by Kurashiki Spinning & Manufacturing Co., Ltd., "EXPEEK")

[0195] [Table 2]

[0196]

[0197] [Table 3]

[0198]

[0199] [Table 4]

[0200]

[0201] [Table 5]

[0202]

[0203] Industrial availability

[0204] According to the present invention, an adhesive tape with excellent adhesion under high-temperature conditions can be provided. Furthermore, according to the present invention, an adhesive composition with excellent adhesion under high-temperature conditions can be provided.

Claims

1. An adhesive tape, characterized in that, It has an adhesive layer. The adhesive layer comprises an acrylic copolymer. The shear storage modulus of the adhesive layer at 150°C, measured by dynamic viscoelasticity at a frequency of 1 Hz, is 8.0 × 10⁻⁶. 4 Pa or higher and 3.0 × 10 5 The loss tangent tanδ at 150°C, measured by dynamic viscoelasticity measurement at a frequency of 1 Hz, is 0.10 or more and 0.40 or less.

2. The adhesive tape according to claim 1, wherein, The acrylic copolymer has structural units derived from (meth)acrylate alkyl esters. The structural units derived from (meth)acrylate alkyl esters include structural units of (meth)acrylate alkyl esters derived from alcohols having 1 or more and 4 or fewer carbon atoms. In the structural units derived from (meth)acrylate alkyl esters, the proportion of structural units derived from alcohol-derived alkyl (meth)acrylate alkyl esters having 1 or more and 4 or less carbon atoms is 50% by mass or more and 100% by mass or less. In the acrylic copolymer, the structural unit derived from (meth)acrylate is present in a proportion of 50% by mass or more and 90% by mass or less.

3. The adhesive tape according to claim 2, wherein, The structural units derived from (meth)acrylate alkyl esters include structural units of (meth)acrylate alkyl esters derived from alcohols having 1 or more and 2 or fewer carbon atoms. In the structural unit derived from (meth)acrylate, the proportion of the structural unit derived from alcohol-derived alkyl (meth)acrylate having 1 or more and 2 or less carbon atoms is 10% by mass or more and 80% by mass or less.

4. The adhesive tape according to claim 1, 2 or 3, wherein, The acrylic copolymer has structural units derived from monomers containing polar functional groups. In the acrylic copolymer, the structural unit derived from the monomer containing polar functional groups accounts for more than 3% by mass and less than 15% by mass.

5. The adhesive tape according to claim 4, wherein, The structural unit derived from a monomer containing a polar functional group comprises at least one structural unit selected from structural units derived from a monomer containing a carboxyl group and structural units derived from a monomer containing a hydroxyl group.

6. The adhesive tape according to claim 1, 2, 3, 4 or 5, wherein, The acrylic copolymer has structural units derived from olefin copolymers with polymerizable unsaturated double bonds at the ends.

7. The adhesive tape according to claim 6, wherein, In the acrylic copolymer, the structural unit derived from the olefin copolymer with polymerizable unsaturated double bonds at the end contains 5% by mass or more and 50% by mass or less.

8. The adhesive tape according to claim 1, 2, 3, 4, 5, 6 or 7, wherein, The weight-average molecular weight of the acrylic copolymer is greater than 750,000 and less than 1,500,000.

9. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7 or 8, wherein, The adhesive layer also contains a silane coupling agent.

10. The adhesive tape according to claim 9, wherein, The content of the silane coupling agent is 0.1 parts by mass or more and 3.0 parts by mass or less, relative to 100 parts by mass of the acrylic copolymer.

11. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, wherein, The adhesive layer also contains a tackifying resin.

12. The adhesive tape according to claim 11, wherein, The tackifying resin comprises at least one selected from terpene phenol resins, rosin resins, and xylene resins.

13. The adhesive tape according to claim 11 or 12, wherein, The content of the tackifying resin is less than 20 parts by weight relative to 100 parts by weight of the acrylic copolymer.

14. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, wherein, The gel content of the adhesive layer is 10% by mass or more and 85% by mass or less.

15. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, wherein, The thickness of the adhesive layer is greater than 5 μm and less than 200 μm.

16. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, having a substrate.

17. The adhesive tape according to claim 16, wherein, The substrate comprises at least one selected from nonwoven fabric, polyester film, polyimide film, polyamide film, polyetheretherketone film, polyphenylene ether film and polyphenylene sulfide film.

18. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17, wherein, The overall thickness of the adhesive tape is more than 50 μm and less than 200 μm.

19. The adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18, for securing electronic device components or vehicle components.

20. An adhesive tape, characterized in that, It has an adhesive layer. The adhesive layer contains an acrylic copolymer having structural units derived from alkyl (meth)acrylates, structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds, and structural units derived from monomers containing polar functional groups. The structural units derived from (meth)acrylate alkyl esters include structural units of (meth)acrylate alkyl esters derived from alcohols having 1 or more and 4 or fewer carbon atoms. In the structural units derived from (meth)acrylate alkyl esters, the proportion of structural units derived from alcohol-derived alkyl (meth)acrylate alkyl esters having 1 or more and 4 or less carbon atoms is 50% by mass or more and 100% by mass or less. In the acrylic copolymer, the structural units derived from (meth)acrylate alkyl esters account for 50% to 90% by mass or more. In the acrylic copolymer, the structural units derived from monomers containing polar functional groups account for 3% to 15% by mass. The weight-average molecular weight of the acrylic copolymer is greater than 750,000 and less than 1,500,000.

21. The adhesive tape according to claim 20, wherein, The structural units derived from (meth)acrylate alkyl esters include structural units of (meth)acrylate alkyl esters derived from alcohols having 1 or more and 2 or fewer carbon atoms. In the structural unit derived from (meth)acrylate, the proportion of the structural unit derived from alcohol-derived alkyl (meth)acrylate having 1 or more and 2 or less carbon atoms is 10% by mass or more and 80% by mass or less.

22. The adhesive tape according to claim 20 or 21, wherein, The structural unit derived from a monomer containing a polar functional group comprises at least one structural unit selected from structural units derived from a monomer containing a carboxyl group and structural units derived from a monomer containing a hydroxyl group.

23. The adhesive tape according to claim 20, 21 or 22, wherein, In the acrylic copolymer, the structural unit derived from the olefin copolymer with polymerizable unsaturated double bonds at the end contains 5% by mass or more and 50% by mass or less.

24. The adhesive tape according to claim 20, 21, 22 or 23, wherein, The adhesive layer also contains a silane coupling agent.

25. The adhesive tape according to claim 24, wherein, The content of the silane coupling agent is 0.1 parts by mass or more and 3.0 parts by mass or less, relative to 100 parts by mass of the acrylic copolymer.

26. The adhesive tape according to claim 20, 21, 22, 23, 24 or 25, wherein, The adhesive layer also contains a tackifying resin.

27. The adhesive tape according to claim 26, wherein, The tackifying resin comprises at least one selected from terpene phenol resins, rosin resins, and xylene resins.

28. The adhesive tape according to claim 26 or 27, wherein, The content of the tackifying resin is less than 20 parts by weight relative to 100 parts by weight of the acrylic copolymer.

29. The adhesive tape according to claim 20, 21, 22, 23, 24, 25, 26, 27 or 28, wherein, The gel content of the adhesive layer is 10% by mass or more and 85% by mass or less.

30. The adhesive tape according to claim 20, 21, 22, 23, 24, 25, 26, 27, 28 or 29, wherein, The thickness of the adhesive layer is greater than 5 μm and less than 200 μm.

31. The adhesive tape according to claim 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30, having a substrate.

32. The adhesive tape according to claim 31, wherein, The substrate comprises at least one selected from nonwoven fabric, polyester film, polyimide film, polyamide film, polyetheretherketone film, polyphenylene ether film and polyphenylene sulfide film.

33. The adhesive tape according to claim 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31 or 32, wherein, The overall thickness of the adhesive tape is more than 50 μm and less than 200 μm.

34. The adhesive tape according to claim 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32 or 33, for fixing electronic device components or vehicle components.

35. An adhesive composition, characterized in that, The product contains an acrylic copolymer and an organic solvent, wherein the acrylic copolymer has structural units derived from alkyl (meth)acrylates, structural units derived from olefin copolymers with terminal polymerizable unsaturated double bonds, and structural units derived from monomers containing polar functional groups. The structural units derived from (meth)acrylate alkyl esters include structural units of (meth)acrylate alkyl esters derived from alcohols having 1 or more and 4 or fewer carbon atoms. In the structural units derived from (meth)acrylate alkyl esters, the proportion of structural units derived from alcohol-derived alkyl (meth)acrylate alkyl esters having 1 or more and 4 or less carbon atoms is 50% by mass or more and 100% by mass or less. In the acrylic copolymer, the structural units derived from (meth)acrylate alkyl esters account for 50% to 90% by mass or more. In the acrylic copolymer, the structural units derived from monomers containing polar functional groups account for 3% to 15% by mass. The weight-average molecular weight of the acrylic copolymer is greater than 750,000 and less than 1,500,000.

36. The adhesive composition according to claim 35, wherein, The structural units derived from (meth)acrylate alkyl esters include structural units of (meth)acrylate alkyl esters derived from alcohols having 1 or more and 2 or fewer carbon atoms. In the structural unit derived from (meth)acrylate, the proportion of the structural unit derived from alcohol-derived alkyl (meth)acrylate having 1 or more and 2 or less carbon atoms is 10% by mass or more and 80% by mass or less.

Citation Information

Patent Citations

  • Thermally conductive adhesive tape, article and image display device

    JP2015021067A

  • Base material for heat-resistant adhesive tape and heat-resistant adhesive tape composed of the same

    JP2015052050A

  • Double-sided adhesive sheet

    JP2015120876A